2020
DOI: 10.1177/1069072720985037
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Investigation of the Association Between Working Alliance and Outcomes of Individual Career Counseling

Abstract: This article reports on the results of the first meta-analysis of the association between working alliance and outcomes of individual career counseling. This random-effects meta-analysis included 18 published and unpublished studies that produced a weighted mean effect size of r = .42. This effect size was heterogeneous across studies. Separate meta-analyses were conducted for several types of outcomes: Career outcomes, mental health outcomes, and client-perceived quality of the intervention. Average effect si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 61 publications
0
9
0
3
Order By: Relevance
“…Meta-analyses (Brown & Ryan Krane, 2000; Oliver & Spokane, 1988; Ryan Krane, 1999; Spokane & Oliver, 1983; Whiston et al, 1998; Whiston et al, 2017) conducted in the past decades demonstrate that individual career counseling leads to a significant decrease in clients’ career decision difficulties with moderate to large effect sizes ( d s ranging between 0.41 and 1.08). Although previous research supports the effectiveness of individual career counseling on career decision difficulties, this broad range of effect sizes suggests that individual career counseling may lead to various degrees of change across clients (Heppner & Heppner, 2003; Milot-Lapointe, Le Corff, & Arifoulline, 2021). In a series of meta-analyses of 62 career intervention studies including 7725 participants, Ryan Krane (1999) observed that the variability in career choice interventions effectiveness is in large part explained by the components of the interventions.…”
Section: Introductionmentioning
confidence: 73%
“…Meta-analyses (Brown & Ryan Krane, 2000; Oliver & Spokane, 1988; Ryan Krane, 1999; Spokane & Oliver, 1983; Whiston et al, 1998; Whiston et al, 2017) conducted in the past decades demonstrate that individual career counseling leads to a significant decrease in clients’ career decision difficulties with moderate to large effect sizes ( d s ranging between 0.41 and 1.08). Although previous research supports the effectiveness of individual career counseling on career decision difficulties, this broad range of effect sizes suggests that individual career counseling may lead to various degrees of change across clients (Heppner & Heppner, 2003; Milot-Lapointe, Le Corff, & Arifoulline, 2021). In a series of meta-analyses of 62 career intervention studies including 7725 participants, Ryan Krane (1999) observed that the variability in career choice interventions effectiveness is in large part explained by the components of the interventions.…”
Section: Introductionmentioning
confidence: 73%
“…Their advocacy is vindicated by a growing body of evidence of the working alliance's contribution to clients' outcomes of career counseling (e.g., Alchin et al, 2018;Elad-Strenger & Littman-Ovadia, 2012;Masdonati et al, 2009Masdonati et al, , 2014Milot-Lapointe et al, 2018Whiston et al, 2016). Meta-analytic research affirms the importance of practitioners attending to the working alliance throughout the course of counseling (Milot-Lapointe et al, 2021). Research findings published in the career development literature and psychotherapy literature (e.g., Flückiger et al, 2018;Horvath et al, 2011;Martin et al, 2000) justify greater attention to the practitioner-client relationship and the factors that influence its effects on clients' experiences and the outcomes of counseling interventions.…”
Section: Working Alliance: the Crucible Of Counseling/ Psychotherapymentioning
confidence: 99%
“… 2002 ) und der individuellen Karriereberatung (Milot-Lapointe et al. 2021 ). Dies unterstreicht die Schlüsselrolle der Arbeitsbeziehung in professionellen zwischenmenschlichen Interaktionen.…”
Section: Das Konzept Der Arbeitsbeziehungunclassified
“…B. auch in der individuellen Karriereberatung (Milot-Lapointe et al. 2021 ) finden. Dies könnte daran liegen, dass Coachees die Arbeitsbeziehung als Indikator nutzen, um die Qualität der Intervention insgesamt zu bewerten (ebd.).…”
Section: Bedeutung Der Arbeitsbeziehung Im Coachingunclassified
See 1 more Smart Citation